Spectral Line Shapes of He I Line 3889 Å - Omar, B.; González, M.; Gigosos, M.; Ramazanov, T.; Jelbuldina, M.; Dzhumagulova, K.; Zammit, Mark; Fursa, Dmitry; Bray, Igor (MDPI AG, 2014)
Spectral line shapes of neutral helium 3889 Å(23S–33P) transition line are calculated by using several theoretical methods. The electronic contribution to the line broadening is calculated from quantum statistical many-particle theory by using thermodynamic Green's function, including dynamic screening of the electron-atom interaction. The ionic contribution is taken into account in a quasistatic approximation, where a static microfield distribution function is presented. Strong electron collisions are consistently considered with an effective two-particle T-matrix approach, where Convergent Close Coupling method gives scattering amplitudes including Debye screening for neutral helium. Then the static profiles converted to dynamic profiles by using the Frequency Fluctuation Model. Furthermore, Molecular Dynamics simulations for interacting and independent particles are used where the dynamic sequence of microfield is taken into account. Plasma parameters are diagnosed and good agreements are shown by comparing our theoretical results with the recent experimental result of Jovićević et al. (J. Phys. B: At. Mol. Opt. Phys. 2005, 38, 1249). Additionally, comparison with various experimental data in a wide range of electron density ne ≈ (1022− 1024)m−3 and temperature T ≈ (2−6) × 104 K are presented.